TUTOR PERFORMANCE ON FACE TO FACE TUTORIAL IN THE PERSPECTIVE OF UPBJJ UT BANJARMASIN - St Aisyah; Yuli Triana (Universitas Lambung Mangkurat, 2021)
The Open University regularly and continuously carries out internal and external audits of the academic administration process both at UT Central and throughout UPBJJ in Indonesia. From the results of monitoring the Face-to-Face Tutorial process carried out at UPBJJ Banjarmasin, especially for Bidikmisi students, it turns out that there are still shortcomings, mainly because of direct monitoring of the working group for the management of Face-to-face Tutorials is rather difficult due to limited funds and current regulations. From the results of the survey distribution and direct monitoring of researchers at the Banjarmasin pokjar as well as document analysis through the results of filling out questionnaires distributed to Bidikmisi students, it appears that there are still some shortcomings in the implementation of Face-to-face Tutorials. Some deficiencies can actually be avoided if the tutor is disciplined in carrying out the standard operating procedures that have been given to them during the briefing before the implementation of the activity. The limited ability of UPBJJ to monitor evaluations at the management working group for these activities means that there are still tutors who lack discipline, especially in the implementation and reporting of activities. There is also a shortage that is difficult to avoid, namely the lack of qualified tutors who are domiciled in areas near the working groups that partner with UT.